Acoplamento do direito internacional tributário ao direito interno - Rodrigues, Rodrigo Dalcin (2007)
This paper aims at analysing the relationship through which is established a liaison of the international tax law (in means of treaties) with the Brazilian law arrangement, comparing it to the approach given by the doctrine to this matter. This paper aims, as well, at identifying and describing the way through which the laws created in ensemble by States are applicable under real tax-related situations both for the payer and the taxed object. Besides, it was also analysed the corroborations given to the characterisation and definition of the law underscoring the language in use, and its prescriptive function, as well as the laws makeup, digressing the enunciated-enunciation, the enunciated-enunciated, the prescriptive enunciations, rules, principles and law norms. Then the expiry and the efficiency are defined as requirements imposed by the laws to their own promptness, as the law regulates its own production. It was also conducted an enquiry of the steps followed by the creation of a tax-related international treaty, stressing the legitimate ones to accomplish it, as well as the procedures to be observed in its production and enforcement, through the international and home law perspectives. Bringing the paper to completion there is an explanation on the divergence that lies in the comprehension and description of the connection of the international tax law and the intern home law. The conclusion obtained is that the Brazilian law allows the application of international laws prior to the home ones, handicapping the efficiency of home laws until the treaties are brought to an end